An Analysis of Speaking Activities in English Practice Class for Midwifery Students - Helfany Amsa (Jurnal Multidisiplin Madani, 2022)
Speaking skill is important for every people, the success of communication is depend on the speaking skill. This was aim at finding out, analysing and describing about speaking activities in English practice class for midwifery students at Politeknik Kesehatan Siteba Padang. This study focused on the teaching learning process in the class, the interaction between lecturer and students during the teaching learning process. This study also focused on the students’ problem with speaking activities The research design in this study was a case study. The data was collected through observation in English practice class and interview then the data could be analyzed completely. The finding of this study showed that in pre speaking activity, two kinds of activity did not find during observation. They were telling the purposes of speaking lesson and showing the format of speaking lesson. In whilst speaking activity, all of the activities were done by the lecturer and the students. On the other hand, there was no activity for post speaking activity. Besides, the students were shy and afraid in practicing Englih through speaking in class.